Medicolegal Investigation of Medical Negligence in India: A Report of Forensic Autopsy Case - Raktim Pratim Tamuli (Wolters Kluwer Medknow Publications, 2016)
In general negligence means failure to take proper care over something and according to law negligence means breach of a duty of care which results in damage. Medical negligence is not very uncommon; every now and then cases of medical negligence are reported in the electronic media. Medical Negligence is doing something that one is not supposed to do, or failing to do something that one is supposed to do. Role of Forensic Pathologist in cases of Medical Negligence is always unquestionable. Forensic Pathologists need to explore and maintain a high degree of transparency between the doctors, patients and the law enforcing agencies. In the present case, a person was attacked by a wild animal and he fell down on a rough surface. Immediately he was rushed to a local hospital. The treating doctor stitched the external injury and allowed him to go home; he neither advised any investigation nor kept him under observation to rule out any internal injury. After 12 hours the victim succumbed to death. At autopsy a fractured skull with underlying subdural haemorrhage was noticed. Was not the treating doctor negligent in this case? Were the protocols followed? What should be the role of a Forensic Pathologist in such kind of cases?